THE IMAGE OF AN ARTIST IN UZBEK AND WORLD LITERATURE (Scientific journal of the Fergana State University, 2023)
The article investigates artistic-aesthetic feartures of artist image in Uzbek and World literature. The interpretation of creative artist as an aesthetic ideal person, feartures of character's spiritual world as a creative person, issues of an individual and society are considered in comparative aspect. The image of an artist is investigated comparativly from the viewpoint of national literature peculiarities and certain historical period